Retail consumer protection in Singapore. - Goh, Teng Yin. (2008)
This project sets out to examine consumers' attitude on this topic and evaluate the adequacy of our consumer protection laws. It studies the available defenses consumers have against unscrupulous traders, looks at the only consumer advocate in Singapore, CASE, as well as consumers' perception of it. The report also introduces the Fair Trading Act proposed by CASE and presents the need for its implementation.